Infectious Salpingitis in an Ornamental Frizzle Hen: A Case Report, Diagnosis and Treatment - Salavati, Ali; Riahi, Amin; Sharifi Moghadam, Amirhossein; Mahdipour, Maryam; Dolatyabi, Sara (Journal of Poultry Sciences and Avian Diseases, 2023)
Salpingitis is a common inflammatory complication in ornamental chickens that occurs due to infectious and non-infectious agents. This disease can cause symptoms such as depression, halted egg laying, swelling of the abdominal area, and breathing difficulities. This report investigates a 3-year-old Frizzle hen presenting with severe anorexia, halted egg laying, decreased activity, depression, and difficulty breathing. Ultrasound examinations and hematology tests were conducted for further differential diagnosis, confirming an inflammatory lesion in the oviduct. The tests were additionally utilized to assess the effectiveness of antibiotic therapy as a treatment measure. This report details the diagnosis, treatment, and evaluation of its effectiveness in a domestic ornamental chicken exhibiting clinical signs indicative of possible lesions in the reproductive system or the presence of free fluids in the coelomic cavity. Following initial examinations, ultrasonography, and hematology tests, salpingitis was confirmed with active involvement of an infectious agent, and the likelihood of ascites due to liver issues was ruled out.. Due to the bird owner’s preference against surgical intervention, a broad-spectrum antibiotic treatment utilizing gentamicin and lincospectin was selected. The clinical condition of the bird improved significantly after five days of treatment, and the ultrasonography and hematology tests were repeated, which showed the progression of the lesion from an active infection to a chronic caseous infection. This report emphasizes the importance of using paraclinical tests in diagnosing genital disorders, especially salpingitis, and evaluating the effectiveness of the treatment strategy.